1975
DOI: 10.1111/1523-1747.ep12598085
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Keratohyalin: Anatomical, Histochemical, Ultrastructural, Immunologic, And Biochemical Studies

Abstract: Salt extraction studies showed that keratohyalin (KH) could be solubilized and extracted from fresh bovine hoof epidermis. The solubility of KH varied in relation to the molarity of the salt solution used for extraction. Using this information, the extracted KH was aggregated in vitro by dialyzing the high salt extract against distilled water. Histochemical, ultrastructural, and immunologic studies of the resultant particles or macroaggregates showed that the latter had the same properties and immunogenicity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

1976
1976
2007
2007

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 27 publications
0
15
0
1
Order By: Relevance
“…She stated that granules might be keratohyaline granules in nature. The studies on the histochemical and the chemical properties of keratohyaline granules (Van Scott 1951; Matoltsy 1962; Szodoray and Nagy 1964;Ugel 1975) have shown that they might be distinct from the peridermal granules. Jenson and Mottet (1970) reported the peridermal granules appeared in the skin culture of the five-day-old chick embryo and Voigt and Fusenig (1979) observed the appearance of these granules in the skin culture of newborn mice.…”
Section: Discussionmentioning
confidence: 99%
“…She stated that granules might be keratohyaline granules in nature. The studies on the histochemical and the chemical properties of keratohyaline granules (Van Scott 1951; Matoltsy 1962; Szodoray and Nagy 1964;Ugel 1975) have shown that they might be distinct from the peridermal granules. Jenson and Mottet (1970) reported the peridermal granules appeared in the skin culture of the five-day-old chick embryo and Voigt and Fusenig (1979) observed the appearance of these granules in the skin culture of newborn mice.…”
Section: Discussionmentioning
confidence: 99%
“…The keratohyalin-granule-associated macroaggregates are histidine-rich proteins [17][18][19], In view of their presumable func tion in the differentiation process of the epidermis, they are designated as filament aggregating proteins [20][21][22], In a multistep process of phosphorylation and déphos phorylation, the histidine-rich alkaline pro teins become filament-aggregating proteins (filaggrin) [23,24], Protein analyses with the aid of the SDS-PAGE show that specifically retinoids with known antipsoriatic activity, such as et retinate and arotinoid ethylester [25,26], biochemically increase the synthesis of keratohyalin-granule-macroaggregates (his tidine-rich proteins), whereas retinoids with low antipsoriatic activity, such as all-rra/ts'-rctinoic acid and 13-m-retinoic acid [27,29], tend to inhibit this protein fraction (R;).…”
Section: Discussionmentioning
confidence: 99%
“…The proteins of the keratohyalin granules in the Stratum granulosum were extracted according to Ugel (1975) and Ugel and Idler (1972) from some of the samples (2 x 2 x 5 mm 3 ) that were obtained from the right hoof sections by incubating the specimens in a 1 molar solution of potassium phosphate (pH 7.0) for twelve hours. Subsequently, the specimens were rinsed in phosphate puffer and processed for the transmission electron microscopic study as described above.…”
Section: Chemistrymentioning
confidence: 99%